FACTORS CONTRIBUTING IN MAKING SCHOOL, A CHILD FRIENDLY SCHOOL - Avasthi, Bhawana; Chakravarty, Ritu T.; Jha, Prof. Arbind Kr. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A review study has been done to identify the factors that contribute in making a school, a child friendly school. Child friendly school is a place where student feels at home. Child friendly school not only provides effective emotional support to the students but also provides all the basic amenities required in school campus.Studies conducted between 2013 to 2023 have been selected for this review study. This study revealed that there are number of factors that contribute in making a school, a child friendly school. Some of those factors are physical infrastructure, teaching methods, teachers attitude towards students, positive environment etc.